Bilosomes and Biloparticles for the Delivery of Lipophilic Drugs: A Preliminary Study - Maddalena Sguizzato; Francesca Ferrara; Nada Baraldo; Agnese Bondi; Annunziata Guarino; Markus Drechsler; Giuseppe Valacchi; Rita Cortesi (MDPI AG, 2023)
In this study, bile acid-based vesicles and nanoparticles (i.e., bilosomes and biloparticles) are studied to improve the water solubility of lipophilic drugs. Ursodeoxycholic acid, sodium cholate, sodium taurocholate and budesonide were used as bile acids and model drugs, respectively. Bilosomes and biloparticles were prepared following standard protocols with minor changes, after a preformulation study. The obtained systems showed good encapsulation efficiency and dimensional stability. Particularly, for biloparticles, the increase in encapsulation efficiency followed the order ursodeoxycholic acid < sodium cholate < sodium taurocholate. The in vitro release of budesonide from both bilosytems was performed by means of dialysis using either a nylon membrane or a portion of Wistar rat small intestine and two receiving solutions (i.e., simulated gastric and intestinal fluids). Both in gastric and intestinal fluid, budesonide was released from bilosystems more slowly than the reference solution, while biloparticles showed a significant improvement in the passage of budesonide into aqueous solution. Immunofluorescence experiments indicated that ursodeoxycholic acid bilosomes containing budesonide are effective in reducing the inflammatory response induced by glucose oxidase stimuli and counteract ox-inflammatory damage within intestinal cells.